Assessing Mental Pain as a Predictive Factor of Suicide Risk in a Clinical Sample of Patients with Psychiatric Disorders - Marta Ielmini; Giulia Lucca; Eric Trabucchi; Gian Luca Aspesi; Alessandro Bellini; Ivano Caselli; Camilla Callegari (Behavioral Sciences, 2022)
According to contemporary suicidology, mental pain represents one of the main suicide risk factors, along with more traditional constructs such as depression, anxiety and hopelessness. This work aims to investigate the relationship between the levels of mental pain and the risk to carry out suicide or suicide attempt in the short term in order to understand if a measurement of mental pain can be used as a screening tool for prevention. For this purpose, 105 outpatients with psychiatric diagnosis were recruited at the university hospital of Varese during a check-up visit and were assessed by using psychometric scales of mental pain levels, hopelessness, anxiety and depression. Clinical and sociodemographic variables of the sample were also collected. A period of 18 months following the recruitment was observed to evaluate any suicides or attempted suicides. Subjects numbering 11 out of 105 committed an attempted suicide. From statistical analyses, high values of the Beck Depression Inventory (BDI-II), Mental Pain Questionnaire (OMMP) and Hamilton Rating Scale for Depression (HAM-D) scales showed a significant association with the risk of carrying out a suicide attempt and, among these, OMMP and BDI-II showed characteristics of good applicability and predictivity proving suitable to be used as potential tools for screening and primary prevention of suicidal behavior.